2010
DOI: 10.1002/hep.23645
|View full text |Cite
|
Sign up to set email alerts
|

Macroautophagy and Chaperone-Mediated Autophagy Are Required for Hepatocyte Resistance to Oxidant Stress

Abstract: The function of the lysosomal degradative pathway of autophagy in cellular injury is unclear, because findings in nonhepatic cells have implicated autophagy as both a mediator of cell death and as a survival response. Autophagic function is impaired in steatotic and aged hepatocytes, suggesting that in these settings hepatocellular injury may be altered by the decrease in autophagy. To delineate the specific function of autophagy in the hepatocyte injury response, the effects of menadione-induced oxidative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 36 publications
4
100
1
2
Order By: Relevance
“…HCV might usurp the autophagy pathway to use it as a mechanism for initiating HCV RNA replication and thereafter, it might inhibit auto lysosome maturation to protect itself from xenophagic degradation [71,76]. Autophagy facilitates inflammation resolution through suppression of inflammasome activation [77], removal of apoptotic corpses [78] and cell protection from oxidative stress through mitophagy [79]. This could explain our results as well as similar previous reports [79 -82].…”
Section: Discussionsupporting
confidence: 88%
“…HCV might usurp the autophagy pathway to use it as a mechanism for initiating HCV RNA replication and thereafter, it might inhibit auto lysosome maturation to protect itself from xenophagic degradation [71,76]. Autophagy facilitates inflammation resolution through suppression of inflammasome activation [77], removal of apoptotic corpses [78] and cell protection from oxidative stress through mitophagy [79]. This could explain our results as well as similar previous reports [79 -82].…”
Section: Discussionsupporting
confidence: 88%
“…(b) Lipotoxicity from the saturated FFA palmitate may be mediated in part by its ability to inhibit lipophagy, resulting in decreased levels of b-oxidation and palmitate metabolism, which increase cellular levels of palmitate to trigger apoptosis of atg5 sensitized hepatocytes to death from nontoxic levels of oxidative stress from the superoxide generator menadione and increased cell death from toxic levels of oxidant stress. 72 In the absence of autophagy, menadione-induced decreases in cellular rates of b-oxidation and ATP content were amplified and sustained rather than transient. These findings suggest that lipophagy-generated FFAs are critical to sustain rates of b-oxidation sufficient to maintain cellular energy homeostasis under oxidant stress.…”
Section: Lipophagy Mediates Resistance To Cell Deathmentioning
confidence: 99%
“…Accumulating evidence using pro-oxidant compounds has suggested that autophagy represents a general inducible response to oxidative stress (22,144,145,154,181). Additionally, autophagy can be modulated during altered states of oxygen tension, including hyperoxia, and hypoxia, corresponding to increased or decreased pO 2 , respectively (91,171).…”
Section: Autophagy In Oxidative Cellular Stressmentioning
confidence: 99%
“…These effects of exogenous H 2 O 2 on autophagy could be inhibited by synthetic antioxidants (22). Autophagy can also be upregulated by ROS generated from redox-cycling compounds, such as menadione (2-methylnaphthalene-1,4-dione), which produce intracellular H 2 O 2 and O 2 -by electron transfer reactions in the mitochondria (181). In addition to macroautophagy, recent studies suggest that chaperone-mediated autophagy can be induced by menadione and may assist in the processing of oxidatively-modified proteins (72).…”
Section: Autophagy In Oxidative Cellular Stressmentioning
confidence: 99%